2021
DOI: 10.3390/app11135826
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Machine-Learning-Enabled Method for Efficient Research in Ethnopharmacology. The Case of the Southern Balkans and the Coastal Zone of Asia Minor

Abstract: Ethnopharmacology experts face several challenges when identifying and retrieving documents and resources related to their scientific focus. The volume of sources that need to be monitored, the variety of formats utilized, and the different quality of language use across sources present some of what we call “big data” challenges in the analysis of this data. This study aims to understand if and how experts can be supported effectively through intelligent tools in the task of ethnopharmacological literature res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Bifulco, Cirillo, Esposito, Guadagni and Polese [5] released a document presenting an intelligent system which is tested especially in the field of e-procurement to support organizations in the focused crawling of artefacts (such as calls for tender, equipment, policies, market trends, and so on) of interest from the web, semantically matching them against internal big data and knowledge sources [5]. A comparable document is also found in the field of ethnopharmacology written by Axiotis, Kontogiannis, Kalpoutzaki and Giannakopoulos [6]. Alarte and Silva [7] discuss the problem of only extracting the relevant content from a website, i.e., ignoring content such as menus, advertisements, copyright notices, and comments.…”
Section: Related Workmentioning
confidence: 99%
“…Bifulco, Cirillo, Esposito, Guadagni and Polese [5] released a document presenting an intelligent system which is tested especially in the field of e-procurement to support organizations in the focused crawling of artefacts (such as calls for tender, equipment, policies, market trends, and so on) of interest from the web, semantically matching them against internal big data and knowledge sources [5]. A comparable document is also found in the field of ethnopharmacology written by Axiotis, Kontogiannis, Kalpoutzaki and Giannakopoulos [6]. Alarte and Silva [7] discuss the problem of only extracting the relevant content from a website, i.e., ignoring content such as menus, advertisements, copyright notices, and comments.…”
Section: Related Workmentioning
confidence: 99%
“…Observe that in our binary reward function setting the harvest rate is equivalent to the agent's average cumulative reward, and thus to an RL metric [34]. Also, we discuss the number of fetched web sites (domains), considering that a web site is relevant if it contains at least one relevant web page.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…They reported that Machine learning-powered research improved the effectiveness and efficiency of the domain expert by 3.1 and 5.14 times, respectively. This was done by fetching 420 relevant ethnopharmacological documents in only seven hours versus an estimated 36 hours of human effort [ 26 ]. The current study documented ethnomedicinal knowledge of medicinal plants in the Shahrbabak region in the southeastern part of Iran, within Kerman Province.…”
Section: Introductionmentioning
confidence: 99%